Injection Molding of Free‐Standing, Three‐Dimensional, All‐Metal Terahertz Metamaterials. Issue 7 (17th April 2014) - Wang, Jinqi; Liu, Shuchang; Guruswamy, Sivaraman; Nahata, Ajay
<x xml:space="preserve">Abstract</x> Fabrication of free‐standing two‐ and three‐dimensional terahertz metamaterials is demonstrated via injection molding of gallium, a metal that melts at temperatures just slightly above room temperature. Molds are created by inscribing the desired microchannel geometries in one or two polydimethylsiloxane (PDMS) films using conventional soft lithography techniques and then reversibly bonding the two films together using van der Waals forces. After heating gallium above its melting point (∼30 °C), the liquid metal is injected into the mold. Surprisingly, the metal does not solidify even after cooling the filled mold at −16 °C for 24 h. However, when the liquid metal comes into contact with solid gallium at room temperature, the entire metal device solidifies within the mold immediately. The PDMS films can then be peeled away, yielding a free‐standing solid gallium structure. A 2D split ring resonator‐based metamaterial is fabricated and three different approaches for creating 3D metamaterials are demonstrated: a multilayer stack, a manually folded structure that maintains its shape after folding, and a directly injection molded 3D structure. The transmission properties of these devices are measured using terahertz time‐domain spectroscopy and are shown to not suffer from limitations imposed by substrates.